Etika Bisnis Islam dalam Khiyar Jual Beli dengan Sistem Cash on Delivery di Ponorogo - Hasanah, Renda Putri; Kadenun, Kadenun; Nafi'ah, Nafi'ah (Indonesian Journal of Islamic Economics and Finance, 2021)
This research is motivated by buying and selling second hand cellphones with a cash on delivery system that is rife in the city of Ponorogo. In practice, sellers and sellers offer their wares through the Second Ponorogo HP Buy and Sell Forum group. In their activities, the buyer feels disadvantaged by the seller due to the seller's dishonest and fraudulent attitude regarding the quality and condition of the second hand cellphone being sold. The sale and purchase (COD) cash on delivery earlier has caused confusion and disputes for one of the parties, because of hidden defects. This study uses field research methods (field research) with a qualitative approach. The data used is the Second Ponorogo HP buying and selling forum contract and the khiyar practice of the Second Ponorogo HP buying and selling forum. The data sources for this research are informants who are involved and active in the Second HP Second HP Sale and Purchase Forum Ponorogo. This study resulted in; The sale and purchase contract at the Second Ponorogo HP Buying and Selling Forum was in accordance with Islamic law and Islamic ethics with the fulfillment of the pillars and conditions of sale and purchase. However, the contract was flawed due to the element of fraud on the quality of the cellphone. While in the practice of Khiyar in The Second Ponorogo HP Sale and Purchase Forum is included in the khiyar Majlis, meaning that the buyer and seller have the right to continue or cancel the transaction before leaving the place of transaction. Judging from the percentage, Islamic ethics in the practice of buying and selling above has not been fully implemented.